Peningkatan Kapasitas Mengajar Guru menggunakan Media Pembelajaran Digital di SDN 14 Bonto-Bonto Kabupaten Pangkep - Anugrayani Bustamin; Indrabayu -; Ingrid Nurtanio; Christoforus Yohannes; Zulkifli Tahir; A. Ais Prayogi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
The application of digital technology can provide solutions to community problems, especially in the education sector. But there are still many teachers whose teaching abilities have not been supported by these digital technologies. SDN 14 Bonto-Bonto located in Pangkep Regency is the place for the digital learning training process as well as a form of community service carried out by the team of the Informatics Engineering Department of the Faculty of Engineering, Hasanuddin University. This activity is also a venue for socialization and introduction of research results from lecturers and students. Digital learning models can be divided into 2 namely electronic based learning and internet based. Some digital learning methods taught include Augmented Reality, Mind Mapping, and Educational Games. Augmented Reality is a technology that involves overlaying computer graphics in the real world, where three-dimensional virtual worlds can be brought into real-world environments in real-time. Learning to use AR makes students' visual appeal in learning as well as educational games. Mind Mapping is a learning method in the form of visualizing ideas, thoughts or plans to form interconnected diagrams. With this method, students are trained to think structured and easy to solve problems. Mind mapping application itself has been widely available and can be downloaded for free. The training in developing digital learning media that is held is expected to help teachers and students understand the concepts while at the same time foster motivation in learning. This service activity also adds insight to teachers about new learning methods that can make the learning process more enjoyable.